METHODLOGY FOR DEVELOPING CHILDREN’S GRAMMATICALLY CORRECT SPEECH IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Abduraimova Sevara Sodiq qizi; Abdukaimova Sitora Alisher qizi (TADQIQOTLAR, 2025)
Abstract:  This  research  paper  examines  the  methodology  for  developing grammatically  correct  speech  among  preschool  children.  It  explores  linguistic, psychological, and pedagogical foundations of grammar development, identifies key factors influencing children’s  speech, and analyzes effective methods and approaches used in preschool educational institutions. The study  emphasizes the importance  of communicative,  play-based,  and  integrated  learning  environments.  Practical recommendations, classroom activities, and teacher strategies are provided to support the development of children’s grammatically correct speech. The paper concludes with an overview of challenges and solutions in early grammar instruction.